Reinnervation of Free Nipple Grafts Associated With Improved Erection Function - Katya Remy, MD; Seth E. Fruge, MD; Ian L. McCulloch, MD; Kristyn Vicente, BA; Makayla Kochheiser, BA; Katherine H. Carruthers, MD; William G. Austen, Jr, MD; Lisa Gfrerer, MD, PhD; Ian L. Valerio, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Most patients undergoing breast surgery with free nipple grafts lose nipple erection (NE) function. This study aimed to evaluate the effect of nerve preservation and reconstruction with targeted nipple–areola complex reinnervation (TNR) on NE following gender-affirming mastectomy with free nipple grafting. Methods:. Patients undergoing gender-affirming mastectomy with free nipple grafts were prospectively enrolled. Subjects who underwent TNR were compared with controls who did not undergo TNR. Postoperative patient-reported NE function was scored using a 4-point Likert scale. Objective NE evaluation consisted of the change in areola circumference and nipple height following cold application using a thermal device and 3-dimensional imaging. Results:. Twenty patients (11 subjects and 9 controls) with comparable age, body mass index, and mastectomy weight were included. At an average follow-up of 16.8 (±7.0) months, significantly more subjects reported NE than controls (72.8% versus 38.9%, P = 0.03), with a higher median NE score (3 [range 1–4] versus 1 [range 1–2], P = 0.0005). Following cold application, subjects had a greater mean reduction in areola circumference (−4.16 ± 3.3 versus −1.67 ± 1.9 mm, P = 0.02) and a greater mean increase in nipple height (+0.86 ± 0.8 versus +0.37±0.3 mm, P = 0.04) compared with controls. Improved patient-reported NE function correlated with better cold detection thresholds (P = 0.01). Conclusions:. TNR was associated with improved patient-reported and objective NE following gender-affirming mastectomy. Improved NE correlated with improved cold detection, suggesting the role of both sensory and autonomic innervation in mediating NE.